2018
DOI: 10.31055/1851.2372.v53.n2.20577
|View full text |Cite
|
Sign up to set email alerts
|

An improved staining protocol for the assessment of arbuscular mycorrhizal in bryophytes

Abstract: The most accepted method for staining arbuscular mycorrhiza (AM) in vascular plants has been one proposed by Phillips & Hayman in 1970. In particular, for the study of AM in bryophytes (s.l.) [Anthocerotophyta, Bryophyta (s.s.), Marchantiophyta] some authors have introduced modifications to this technique. Even though all these protocols stain AM, their main disadvantage is related to the result of material maceration (e.g. over-softening or completely destroying plant cells due to the high temperatures us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 8 publications
0
12
0
4
Order By: Relevance
“…Higher concentrations of H 2 O 2 may have increased transparency but were not tested in the current study, as it has been reported by Vierheilig et al (2005) to cause the disintegration of fungal hyphae in the tissue. In order to clear the background from any phenolic-like materials, the roots were immersed in 70% ethanol overnight for fixation prior to the clearing process as this has been reported to cause a partial decolourisation that dehydrates the cells which allow a greater penetration of the KOH (Cottet et al 2018). Incubating the roots in ethanol increased the subsequent penetration of the root tissue by potassium hydroxide and eliminated all unwanted background staining resulting in AMF structures being clearly visible to enable quantification.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Higher concentrations of H 2 O 2 may have increased transparency but were not tested in the current study, as it has been reported by Vierheilig et al (2005) to cause the disintegration of fungal hyphae in the tissue. In order to clear the background from any phenolic-like materials, the roots were immersed in 70% ethanol overnight for fixation prior to the clearing process as this has been reported to cause a partial decolourisation that dehydrates the cells which allow a greater penetration of the KOH (Cottet et al 2018). Incubating the roots in ethanol increased the subsequent penetration of the root tissue by potassium hydroxide and eliminated all unwanted background staining resulting in AMF structures being clearly visible to enable quantification.…”
Section: Discussionmentioning
confidence: 99%
“…For those treatments that included a fixing step, roots were covered with 70% v/v ethanol (~20 mL) as recommended by Fonseca et al (2014) and Cottet et al (2018) and left overnight at room temperature then decanted prior to clearing.…”
Section: Fixingmentioning
confidence: 99%
See 2 more Smart Citations
“…Para observar la colonización por HMA, los gametofitos fueron lavados con agua corriente y preservados en etanol al 70% durante 24 horas a temperatura ambiente; posteriormente se colocaron en cajas de Petri a 50 °C sobre un agitador magnético de calentamiento (VELP Scientifica, Usmate, Velate, Italia), con placa caliente hasta la evaporación total del líquido. Posteriormente, fueron clarificados en hidróxido de potasio al 1% durante 20 minutos a 80 °C; acidificados con ácido clorhídrico al 1% durante 10 minutos a 50 °C y teñidos con azul de tripán al 0.05% durante 20 minutos a 60 °C (Cottet et al, 2018;Cottet y Messuti, 2019). El porcentaje de colonización por HMA se estimó utilizando la presencia o ausencia de las estructuras características de estos hongos con un aumento de 400× en todo el talo (47 talos).…”
Section: Estudio De Colonizaciónunclassified